2009
DOI: 10.2174/1877729500901010015
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation into the Effective Permeability of Porous Media whose Matrices are Composed of Obstacles of Different Sizes

Abstract: A comprehensive experimental investigation has been conducted to determine the effective permeability of fluid saturated porous media consisting of small and large spherical particles. Small and large particles were mixed uniformly at a certain mixture ratio so as to form a vertical porous column. Water was drawn from a reservoir to flow through the vertical tube filled with particles of different sizes. The resulting pressure drops between the inlet and outlet sections of the test column were measured at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Sano et al, [4] measured the effective permeability of fluid saturated porous media consisting of small and large (2), (8) and (10).…”
Section: Comparison With Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sano et al, [4] measured the effective permeability of fluid saturated porous media consisting of small and large (2), (8) and (10).…”
Section: Comparison With Related Studiesmentioning
confidence: 99%
“…They focused on an equivalent continuum model and proposed an analytical expression to determine the effective permeability. Sano et al, [4] extended Liu et al 's [2] work to calculate the effective permeability of a porous medium with impermeable blocks of different sizes. Khajeh and Maijer [5] developed an analytical expression based on a solution to the Brinkman-Darcy equation for the permeability of solidifying hypoeutectic aluminum alloys by considering the microstructure to be a dual-structured porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Sano et al, [3] extended their analytical expression to estimate the pressure drop in the flow in a bed packed with particles of different sizes. They conducted a series of the experiments using a column of particles of different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…They focused on an equivalent continuum model and proposed a mathematical relation for determining the effective permeability. Sano et al [26] extended the work of Liu et al [24] to calculate the effective permeability of a porous medium with obstacles of different sizes. Both studies showed excellent agreement between the permeabilities calculated with the developed mathematical expressions and experimental measurements.…”
Section: Introductionmentioning
confidence: 99%